Suppressed ion chromatography methods for the routine determination of ultra low level anions and cations in ice cores - Curran, MAJ; Palmer, AS (Journal of Chromatography A, 2001)
The concentration of trace ionic species in snow and ice samples was determined using suppressed ion chromatography (IC) with conductivity detection and ultra-clean sample preparation techniques. Trace anion species were determined in a single 24-min run by combining sample preconcentration with gradient elution using Na2B4O7 eluent. The detection limits (ranging from 0.001 to 0.006 M) are the lowest reported in the literature. Cation species were analysed by direct injection of 0.25 ml and isocratic elution with a H2SO4 eluent. The clean preparation techniques showed no evidence of a difference (Student's t-test) between Milli-Q water samples analysed directly and processed Milli-Q ice samples. These robust, ultra-clean IC methods were routinely applied to the analysis of large number of samples to produce a high-resolution trace ion ice core record from Law Dome, East Antarctica. 2001 Elsevier Science B.V.